Analysis of the Application of PSAK 109 to the Management of Zakat, Infaq, and Sadaqah Funds (Dompet Dhuafa Medan Helvetia) - Saragih, Ummi Rahayu; Syafina, Laylan; Nurbaiti, Nurbaiti (PT Mattawang Mediatama Solution, 2024)
The implementation of PSAK 109 aims to guarantee the level of compliance with its implementation by Amil Zakat Institutions and whether they follow sharia principles or not. Definition, Recognition and Measurement, Presentation, and Problems This is related to PSAK 109 which regulates distribution, operational rules and accounting for zakat and infaq/alms. Qualitative research includes this research. For this research, primary and secondary data were used for fact analysis using descriptive analysis to describe a collection of information, presenting facts through an information reduction process and thought-provoking conclusions. The research results show that PSAK 109 has not been fully implemented by Dompet Dhuafa Medan. This research focuses more on reporting ZIS money, while previous research discussed more on the distribution of ZIS funds.